Comparison of moringa oliefera seed oil characterization produced by chemical and mechanical method - Muhamad Khairul Naim, Saad (2015)
In this developed world today, we have many people who concerned about the nature, the energy being used every day, and it effects to our future generation. Moreover, problems regarding to the diease has killed more people. An attempt has been made here to review the nutritive and medicinal value of miracle tree Moringa oleifera. It is established that virtually every part of the tree (leaves, stem, bark, root, flower, seeds, and gum, oil(from seed)) is beneficial in some way hence regarded as the tree with greatest benefits on planet earth. The tree is rich in proteins, vitamins, minerals. All Moringa oleifera food products have a very high nutritional value. They are eaten directly as food, as supplements, and as seasonings as well as fodder for animals. The purpose of the research is to compare Moringa oliefera oil characterization produce by chemically method and mechanically method. The effect of different size of sample in oil extraction using chemically method is also studied. The Moringa oleifera seeds were grinded and the oil is extracted through solvent extraction process using three different size of sample. The average yield was produce are 36.1% for 2mm,40.8% for 1mm and 38.9% for 500μm, for the properties of Moringa oliefera oil was analysed and for the density the value is 873(kg/m3) for mechanically 880(kg/m3) and chemically method. For kinematic viscosity 42.2 for mechanically and 9.12 for chemically method, pH value is 6 for both and cloud and pour point are 18°C and 12°C respectively. For the fatty acid was found the present of Oleic acid is higher about 73.60% from mechanicallyand 75.39 from chemically method. In conclusion, Moringa oleifera seeds oil appear to be an acceptable good source for oil rich in oleic acid that can be used in medical treatment and as an alternative for olive oil.